Case Report: Re-Sensitization to Gefitinib in Lung Adenocarcinoma Harboring EGFR Mutation and High PD-L1 Expression After Immunotherapy Resistance, Which Finally Transform Into Small Cell Carcinoma - Zhai, Xiaoqian; Liu, Jiewei; Liang, Zuoyu; Li, Zhixi; Liu, Yanyang; Huang, Lin; Wang, Weiya; Luo, Feng (Frontiers in Oncology, 2021)
The treatment sequence of immunotherapy (IO) and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) is of great importance for survival of non-small cell lung cancer (NSCLC) patients with EGFR sensitive mutation. Here, we reported an advanced lung adenocarcinoma case concurrent with EGFR sensitive mutation and high PD-L1 expression (>50%) was administrated with gefitinib firstly, and then became resistant to EGFR-TKI. He received the strategy of immunity-combined chemo-radiotherapy and responded significantly. However, the disease re-progressed after 10 months. Surprisingly, the tumor re-sensitized to gefitinib for 13 months. At final, following the treatment pressure of TKI-IO combination therapy-TKI strategy, tumor clone eventually transformed into small cell lung carcinoma (SCLC). For one thing, our study provided novel approach and extended the treatment spectra of overcoming immunotherapy resistance after EGFR resistance in driver oncogene-mutated NSCLC. For another thing, our case is the first time to report that SCLC transformation can be achieved after gefitinib-pembrolizumab-gefitinib resistance in EGFR sensitive mutation NSCLC, providing a new condition for SCLC transformation.